The Relationship Between Education Level and Socioeconomic Status with The Incidence of CED (Chronic Energy Deficiency) Among Pregnant Women - Kaumpungan, Kristesa Lista; Ilmiah, Widia Shofa; Maulina, Rifzul (Jurnal MID-Z (MIDWIFERI ZIGOT), 2024)
Chronic Energy Deficiency (CHD) in pregnant women remains a serious issue in Indonesia, with negative impacts on maternal and fetal health. Education level and socioeconomic status play an important role in the incidence of SEZ, where higher education and better economic status can reduce this risk. This study aims to examine the relationship between education level and economic status with the incidence of SEZ in pregnant women at the Poigar Health Center. The research design used in this study was Analytical Correlation. The approach model used was Cross Sectional to study the relationship between Education Level and Socioeconomic Status on the Incidence of Chronic Energy Deficiency (SEZ) in pregnant women. This study was conducted in the working area of the Poigar Health Center. The population of this study were all pregnant women in the Poigor Health Center working area as many as 30 people, because this study used a total sampling technique, the number of samples was the same as the population. The mresults of the chi-square test on the education level of respondents showed a value of p = 0.045, it can be concluded that the level of education has a relationship with chronic energy deficiency (CHD) in pregnant women while the results of the chi-square test on socioeconomic status also showed a value of p = 0.000, which indicates a statistically significant relationship between socioeconomic status (income) and the incidence.